Establishing Bayley-III cut-off scores at 21 months for predicting low IQ scores at 3 years of age in a preterm cohort. Issue 8 (9th April 2018) - Creighton, Dianne E; Tang, Selphee; Newman, Jill; Hendson, Leonora; Sauve, Reg
Abstract: Objective: To evaluate predictive validity and establish cut-off scores on the Bayley-III at age 21 months that best predict Intelligence Quotient (IQ) scores <70 or <80) at 3 years in a high-risk preterm cohort. Method: Bayley-III evaluations at 21 months corrected age and intellectual assessments, primarily with the WPPSI-III, at 3 years corrected age were conducted with 520 infants born less than 29 weeks gestational age or less than 1250 g birth weight. Receiver Operator Characteristic (ROC) curves were used to establish Bayley-III Cognitive Composite cut-off scores that maximized Sensitivity and Specificity in predicting low IQ. Similar analyses were performed using the Language Composite, and a research derived mean Cognitive-Language Composite. Results: A regression model for the association between 21-month Bayley-III Cognitive Composite and 3-year IQ scores was significant (P<0.0001, Adjusted R 2 =0.36). The ROC area under the Curve was 0.90 for the Cognitive Composite predicting IQ<70. The cut-off score that maximized Sensitivity and Specificity for predicting 3-year IQ<70 was a Cognitive Composite of <80. The ROC Area under the Curve was 0.80 for Cognitive Composites predicting IQ<80 and a Cognitive Composite cut-off score of <90 maximized Sensitivity and Specificity. Conclusion: In this high-risk preterm cohort, there was a strong association between the Bayley-III Cognitive Composite at 21 months and IQ at 3 years. A Cognitive Composite cut-off score of <80 optimized classification of IQ<70 at 3 years, and a Cognitive Composite cut-off score of <90 optimized classification of IQ<80.